Implementation and evaluation of an Epson V800 Scanner and Gafchromic EBT3 Film for use in routine Linac QA and Patient Specific QA checks. (August 2018) - Corbally, Clare; Cronin, John; Woulfe, Peter
Abstract : In order to achieve more conformal dose distributions to the patient forms of radiotherapy delivery have become increasingly complex. With this comes an increased chance of error in delivery and an increased need to verify dose distribution using patient-specific QA. The aim of this project was to evaluate the use of Gafchromic EBT3 film and an Epson V800 scanner in linac QA and patient-specific QA checks. Response of EBT3 was found to be linear and accurate within 3% for a dose range of 0–400 cGy with use of the green channel. Effects of change in orientation showed max variation between two orientations of 1%. Change in response of 6% was shown between scans taken one hour and 24 h post-irradiation confirming that all scans should be taken at the same interval post-irradiation. A 1 h interval was chosen. Variation of position showed max change in response laterally of 6% confirming that scans should be performed in the centre of the scanner bed. Variation in number of warm-up scans showed max deviation of 0.4%. Intra-sheet homogeneity was within 0.8% and inter-sheet homogeneity was within 4%. Using these findings a protocol was devised and three basic fields and three IMRT and VMAT patient plans were measured. After normalisation of dose differences between measured and calculated distributions, EBT3 had similar or higher gamma-index passing rates than those achieved by Octavius detectors. In conclusion the method derived was shown to be a suitable alternative to the 2D arrays and reduced time required for film dosimetry.